2020
DOI: 10.1073/pnas.2000414117
|View full text |Cite
|
Sign up to set email alerts
|

A combination of two human monoclonal antibodies limits fetal damage by Zika virus in macaques

Abstract: Human infection by Zika virus (ZIKV) during pregnancy can lead to vertical transmission and fetal aberrations, including microcephaly. Prophylactic administration of antibodies can diminish or prevent ZIKV infection in animal models, but whether passive immunization can protect nonhuman primates and their fetuses during pregnancy has not been determined. Z004 and Z021 are neutralizing monoclonal antibodies to domain III of the envelope (EDIII) of ZIKV. Together the two antibodies protect nonpregnant macaques a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 55 publications
1
16
0
Order By: Relevance
“…can be modified to prevent interactions with the Fc gamma receptor and that remain protective against viral pathogens 23 .…”
Section: Articlementioning
confidence: 99%
See 1 more Smart Citation
“…can be modified to prevent interactions with the Fc gamma receptor and that remain protective against viral pathogens 23 .…”
Section: Articlementioning
confidence: 99%
“…These interactions can enhance immunity and help clear the pathogen or infected cells, but they can also lead to disease enhancement during Dengue 20 and possibly coronavirus infections 21 . This problem has impeded Dengue vaccine development but would not interfere with the clinical use of potent neutralizing antibodies that can be modified to prevent Fc gamma receptor interactions and remain protective against viral pathogens 22 .…”
mentioning
confidence: 99%
“…These interactions can enhance immunity and help clear the pathogen or infected cells, but they can also lead to disease enhancement during Dengue 13 and possibly coronavirus infections 14 . This problem has impeded Dengue vaccine development but would not interfere with the clinical use of potent neutralizing antibodies that can be modified to prevent Fc gamma receptor interactions and remain protective against viral pathogens 15 .…”
mentioning
confidence: 99%
“…Here, we sought to extend our VLP vaccine development studies to include the rhesus macaque model. Rhesus macaques have been used as models of ZIKV disease and also as vaccine efficacy [ 56 , 63 67 ]. In regard to our NHP ZIKV challenge studies, it was demonstrated that only 3 of 5 alum only immunized control NHP animals demonstrated infection detectable by plaque assay.…”
Section: Discussionmentioning
confidence: 99%